1981
DOI: 10.1159/000232833
|View full text |Cite
|
Sign up to set email alerts
|

Increased Multiclonal Antibody-Forming Cell Activity in the Peripheral Blood of Patients with SLE

Abstract: 21 patients with criteria for systemic lupus erythematosus (SLE) and 12 normal controls were studied for their spontaneous circulating IgM and IgG plaque-forming cells (PFCs) reactive against sheep erythrocytes (SRBC) and against a panel of five haptens. Quantitatively defined active and mildly active SLE patients had significantly elevated IgM- and IgG-producing PFCs in their peripheral blood reactive with the panel of five chemically defined haptens. Those patients having inactive SLE also showed increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Studies at the NIH (some published in Sakane et al 1978, Kumagai et al 1982, Glinski et al 1976, Becker et al 1981, Blaese et al 1980 have demonstrated that patients with SLE and very active multisystem disease have marked increases in all parts of the B-cell generation pathway (Table I). The increase in immunoglobulin-secreting ceils in patients with active lupus is not limited to those producing autoantibodies.…”
Section: Sle Is Characterized By Increases Throughout B-ceu Maturationmentioning
confidence: 99%
“…Studies at the NIH (some published in Sakane et al 1978, Kumagai et al 1982, Glinski et al 1976, Becker et al 1981, Blaese et al 1980 have demonstrated that patients with SLE and very active multisystem disease have marked increases in all parts of the B-cell generation pathway (Table I). The increase in immunoglobulin-secreting ceils in patients with active lupus is not limited to those producing autoantibodies.…”
Section: Sle Is Characterized By Increases Throughout B-ceu Maturationmentioning
confidence: 99%
“…Exogenous IL-6 has been shown to promote murine lupus, while specific monoclonal antibodies (MoAb) to IL-6 and IL-10 delay the development of this disease in NZB/W F 1 mice [20,21]. An intrinsic overproduction of these cytokines might also explain the pre-existing B-cell hyperactive state reported in family members of SLE patients, as well as in lupus patients themselves [22][23][24][25][26]. Defects in responsiveness to IL-10 may enhance the generation of neoantigens on nucleic acids and nuclear proteins during apoptosis, because IL-10 also exerts an inhibitory effect upon the generation of reactive oxygen metabolites, which can modify such antigens [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…7 Conversely, there are cases that show only increased levels of gammaglobulin, or deterioration of spirometry or increased levels of muscle enzymes with no complaints (weakness), and these are typical findings of disease activity. 1,8 Becker et al 9 have also provided details of a form of activity criteria, however this system is rarely mentioned in the literature.…”
Section: Sirmentioning
confidence: 99%